Wildlife Crime and Animal Victims: Improving Access to Environmental Justice in Hong Kong. Issue 3 (3rd July 2019) - Whitfort, Amanda
Abstract: Wildlife crimes are often argued to be victimless, due to the anthropocentric view of crime that dominates policy and policing discourse. Falling outside the normative criminal justice lens, wildlife crimes are not frequently brought to court, and a lack of expertise in policing and prosecuting cases impairs their recognition as serious crimes. When wildlife offences are prosecuted, the tendency to try cases in the magistrates' courts compounds problems with a lack of judicial exposure to this specialised form of crime and limits development of judicial expertise in the field. Lacking legal standing in the court process, harms caused to endangered animals (as individuals or species) are often marginalised from consideration in sentencing decisions. Recognised only as legal property, animals may be forfeited or returned to their lawful owners, in accordance with the court's findings. Focusing on recent developments in criminal justice in Hong Kong and Scotland, this article argues that a more effective justice response to wildlife crime permits recognition of the interests of animals, as victims, in wildlife offences. In both jurisdictions, statements establishing the impact of wildlife crimes are utilised by prosecutors in their presentation of cases at court. Armed with knowledge of the role of animals as individual and species victims of crime, sentences may be passed that take appropriate regard of wild animal suffering, their monetary and conservation value, and the impact of their loss on biodiversity. The use of these statements is allowing for better-informed sentencing decisions in individual cases and improved environmental justice.